THE CORRELATION BETWEEN READING AND LISTENING COMPREHENSION - ISYATUR RADHIYAH (STIT DARUL ULUM KOTABARU, 2021)
Education is the knowledge of putting one’s potentials to maximum use. Without education, no one can find the proper right path in this world. In this modern era, people are demanded to have more than one language. Language as a tool for communication takes an important role in our daily activities. Without communication, we will be left behind. Communication in foreign language is a bridge to get information, knowledge and culture. In education English is an international language. English lesson has four skills that should be mastered by its learners. Those important skills of language are listening, speaking, reading, and writing skill. The four skills should be taught consolidated. Reading gets a high attention because reading is considered as a key of knowledge. Listening, as one of the means of language communication, is used most widely in people’s daily lives. Mastering of reading comprehension will help other aspects (four skills) in language, especially in listening comprehension skills. Because reading and listening are important to master.